2021
DOI: 10.18632/aging.202917
|View full text |Cite
|
Sign up to set email alerts
|

Development of a prognostic index and screening of prognosis related genes based on an immunogenomic landscape analysis of bladder cancer

Abstract: Background: Bladder cancer (BLCA) is one of the most common urinary tract malignant tumors. It is associated with poor outcomes, and its etiology and pathogenesis are not fully understood. There is great hope for immunotherapy in treating many malignant tumors; therefore, it is worthwhile to explore the use of immunotherapy for BLCA.Methods: Gene expression profiles and clinical information were obtained from The Cancer Genome Atlas (TCGA), and immune-related genes (IRGs) were downloaded from the Immunology Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…In this study, we found that IGF1 may contribute to an increase in the levels of native B cell and M2 macrophages. MMP9, as a classical immune-related gene, has been demonstrated to play a vital role in the immune treatment of BLCA ( 28 ). MMP9 contributes to the promotion of the neutrophil-mediated inflammation, indicating its roles in immune infiltrates ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that IGF1 may contribute to an increase in the levels of native B cell and M2 macrophages. MMP9, as a classical immune-related gene, has been demonstrated to play a vital role in the immune treatment of BLCA ( 28 ). MMP9 contributes to the promotion of the neutrophil-mediated inflammation, indicating its roles in immune infiltrates ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that OAS1 could suppress accumulation of excess Poly (ADPribose) (PAR) in response to DNA damage, thereby inhibiting programmed cell death due to energy depletion and/or activation of PAR (Kondratova et al, 2020). Moreover, Qu and colleagues once proposed a IRG-based prognostic index containing AHNAK and OAS1 that could assess immune status and prognosis with BLCA (Qu et al, 2021). Besides, NGF is a member of the neurotrophic factor family that protects peripheral nerve cells (Rocco et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…( 5) the effects of the low CONUT group and high CONUT group on the prognosis of surgical patients were discussed, and the hazard ratio (HR) was provided. (6) the design type of the study is a retrospective study and prospective study. (7) the research, which is rated as high quality by the study quality evaluation system.…”
Section: Literature Search and Eligibility Criteriamentioning
confidence: 99%
“…Any pathological type of bladder cancer has a recurrence, fatal complications, and poor prognosis after treatment. At present, a lot of studies have proved that some genes, the ratio of fibrinogen to serum albumin, the percentage of neutrophils to lymphocytes, and the modified Glasgow Prognostic Score (GPS) can be used to assess the prognosis of BC (5)(6)(7). UTUC includes ureteral cancer and renal pelvic cancer, with a low incidence, accounting for less than 10% of urothelial cancers.…”
Section: Introductionmentioning
confidence: 99%